Defect mediated electronic properties and robust magnetism of two dimensional ε-Mn2O3 - Pankaj Kumar; Renu Singla; Rahul Singla; Sarvesh Kumar; Hardev S. Saini; Manish K. Kashyap (Next Materials)
2D-Mn2O3 is a newly exfoliated two dimensional (2D) analog of bulk manganese (III) oxide which is an intrinsic ferromagnetic material in its pristine form. The detailed structural, electronic and magnetic properties analyses have been carried out using density functional theory (DFT) approach. The calculated results indicate that it is ferromagnetic in pristine form and turns out to be a magnetic semiconductor with a large band gap of 0.98/3.6 eV in the majority/minority spin channel. The presence of a large band gap highly restricts its worth in spintronics and magnetic devices. In addition, Curie Temperature (TC) comes out to be 77 K. Thus to modify its band gap, the efforts have been made to introduce defects in it by removing Mn and O atoms, respectively. The reported results show that the band gap of resulting material after introducing O- vacancy defect gets reduced in both the spin channels to a great extent (0.40/3.31 eV in the majority/minority spin channel). However, with this vacancy defect, the spin magnetic moment gets increased slightly from 4 µB to 4.06 µB per Mn atom which confirms the robustness of spin magnetic moment of Mn atom. These findings show that the resulting 2D-Mn2O3 under study has numerous potential applications in spintronics and memory-based applications.